Amplification of impulsively excited molecular rotational coherence. - Bustard, P; Sussman, B; Walmsley, I (2010)
We propose a scheme for preparation of high-coherence molecular dynamics which are phase stable with respect to ultrashort pulses. We experimentally demonstrate an example of this scheme using a phase-independent, nanosecond-duration, pump pulse to prepare a rotational coherence in molecular hydrogen. This rotational coherence is made phase stable with respect to a separate source of ultrashort pulses by seeding. The coherence is used to generate spectral broadening of femtosecond probe radiation by molecular phase modulation.